Operational performance and energy efficiency of axial harvesters with single and double rotor systems in soybean seed harvest - Jasper,Samir Paulo (2021)
ABSTRACT The decision-making capability of the machine to harvest grains must consider a lower fuel consumption with a higher operating velocity allied to a greater performance of the grain cleaning system, along with lower rates of the damage and waste produced. This study aimed at evaluating the operational performance and the energy efficiency of two axial harvesters, having different trail and separation systems in the soybean seed harvest. The experiment was carried out in a completely randomized block design in 500-m bands, consisting of two factors, namely two axial harvesters (single and double rotor) and six target velocities (3, 4, 5, 6, 7, and 8 km h-1). Regarding the operational energy performance, the hourly fuel consumption, operational speed, operational field capacity, fuel consumption per area and mass of the harvested grain, and the handling capacity of the harvest were evaluated. The harvesting performance parameters, such as the percentage losses in the platform and the trail system, broken grains, impurities, and the pods, which did not undergo threshing, were evaluated. The results obtained showed that the single-rotor harvester had a better energy efficiency, while the double-rotor harvester had a better operational performance. The double-rotor harvester was agronomically more efficient.